(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-194-204 New words of western terminology, such as media communication and other options of media-, have been recently enrolled in professional practice of journalism, in teaching process and scientific reflection in this field. Further understanding of new terminology led to differentiation professional competences in training journalist-to-be and specialists in media communication. Scientific reason for this differentiation has become a problem of high importance. There are many articles on this theme, but they are mostly in conclusion come to mass media processes. Using the methodology of system approach, theory of M. MacLuhan on evolution of media and his methods of paper analysis we tried to show that journalism and media communication represent two different systems. The first one is highly institutionalized, focused on collecting, analysing and delivering information for audience. The second is less controlled and managed. It is focused on interpersonal and group communication inside the system. Key words: media, media communication, journalism, technologies, system